If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -3b = -1(-2 + 4b) -3 + -3b = (-2 * -1 + 4b * -1) -3 + -3b = (2 + -4b) Solving -3 + -3b = 2 + -4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4b' to each side of the equation. -3 + -3b + 4b = 2 + -4b + 4b Combine like terms: -3b + 4b = 1b -3 + 1b = 2 + -4b + 4b Combine like terms: -4b + 4b = 0 -3 + 1b = 2 + 0 -3 + 1b = 2 Add '3' to each side of the equation. -3 + 3 + 1b = 2 + 3 Combine like terms: -3 + 3 = 0 0 + 1b = 2 + 3 1b = 2 + 3 Combine like terms: 2 + 3 = 5 1b = 5 Divide each side by '1'. b = 5 Simplifying b = 5
| 8/5-2=-13 | | 8+7r=-8(r-1) | | -6v-11=4(-2v+6)-1 | | 4.5x-1.5=12 | | -12+4p=-p+3p | | 0=x^4-2x^3-4x^2+2x+3 | | (4x^3+8x)(x^2-3)=0 | | 830+y=520 | | 7x^2=1028 | | x^4+2*x^2*y^2+y^4=2 | | (x^2+y^2)=x^3 | | x^2+y^2=3 | | -4x-8=3x-7 | | 2/7/4/6 | | 40+2x=48 | | 45/27=40/x | | -4/9-1/6 | | 0=-32t^2+64t | | 0=-32t^2+64y | | 1-.75= | | 9-2x=6-c | | (6x+16)*(2x)=(2x+18)*(4x) | | -5/4*2/3 | | 4x+5x+40=180 | | y=6(x+3) | | y=6(x+3)4 | | p/3-3p/8=4 | | 5(2k+4)=6+8k | | 6.3+3.8= | | 39+3a=-8(2a+3)+6 | | 1-x/5=2x+1 | | 21c-18=36 |